Wolves choose ambushing locations to counter and capitalize on the sensory abilities of their prey - Gable, Thomas; Homkes, Austin; Johnson-Bice, Sean; Windels, Steve; Bump, Joseph (Zenodo, 2020)
Wolves ( Canis lupus ) are primarily cursorial predators, but they use ambush strategies to hunt beavers ( Castor canadensis ). Terrestrial beaver activity is predictable because beavers use well-defined, conspicuous habitat features repeatedly. Thus, studying where wolves wait-in-ambush for beavers provides a unique opportunity to understand how predators choose ambush locations in relation to prey activity. We searched 11,817 clusters of GPS-locations from wolves in the Greater Voyageurs Ecosystem, Minnesota, USA and documented 748 ambushing sites and 214 instances where wolves killed beavers. Wolves chose ambush locations: 1) with olfactory concealment to avoid detection from the highly-developed olfactory senses of beavers, and 2) close (generally <5 m) to beaver habitat features to take advantage of beavers' inability to visually detect motionless predators. Our work describes in detail the ambush strategies wolves use to hunt beavers, and continues to overturn the traditional notion that wolves rely solely on cursorial hunting strategies. We also demonstrate that ambush predators can anticipate the movements and behavior of their prey due to a fundamental understanding of their prey's sensory abilities. Wolves therefore, and likely ambush predators in general, appear capable of simultaneously accounting for abiotic and biotic factors when choosing ambush locations, ultimately allowing them to counter the defenses and exploit the sensory deficiencies of their prey. For the AmbushingAttempts_Data_2015-2019 data, the fields are as follows below. Note: each row of data is a unique ambushing attempt. Hunting Attempt ID: an unique ID assigned to each ambushing attempt identified Wolf ID: the wolf that made a specific ambushing attempt 1st Beaver Feature: A beaver feature (e.g. feeding trail, dam) a wolf waited to during an ambushing attempt. If the wolf only waited next to one feature during the attempt than only this field (1st Beaver Feature) will include data whereas the fields "2nd Beaver Feature" and ...